(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
State status of its native language and functioning of a state language in all the spheres of social life is supposed to be one of the basic manifestations of a nation self-assertion and consolidation. To achieve this aim it is obligatory to introduce state language policy according to Constitutional norms and international law obligations of Ukraine. The present investigation is a fragment of a scientific theme: «Study of values in the system of science and culture», being carried out by the department of social sciences and Ukrainology of Bukovinian state medical university.